The Meaning of Soul in Ælfric’s “Catholic Homilines” - Inčiuraitė, Lina (Verbum, 2010)
Ælfric’s writings accurately reflect the early medieval or Anglo-Saxon deep contemplation of the universe, for Anglo-Saxon scholar’s ideas were culture-specific. Meanwhile, “Catholic Homilies” reveal the author’s personal style as well as the didactic concerns to teach his audience moral and spiritual values. In his sermons, the Anglo-Saxon abbot of Eynsham has an abiding interest in doctrinal issues namely salvation, baptism, resurrection of the body, the soul and body dualism. The abbot identified the soul with the tenet of immortality. Therefore, the analysis focuses on the meaning of soul in Ælfric’s “Catholic Homilies”. The article advocates an interdisciplinary approach which embraces the fields of cognitive semantics, the history of the English language, culturology, philosophy, and theology. As far as Ælfric’s Sermons are concerned, they are regarded as a considerable and invaluable resource for a wide variety of linguistic and theological investigations. In his “Catholic Sermons”, the importance of soul and its faculties are indicated by the size and diversity of the vocabulary. The research reveals the connotations of sawel, i. e. sawel as a superordinate, and other words (such as gast ‘soul, spirit’, mōd ‘mind, soul, heart, spirit, mood’, gemynd ‘memoria’, gescead ‘ratio and wylla ‘voluntas’) as its hyponyms.
Keywords: connotation; superordinate; hyponym; rational soul; mind; memory; spirit